2007
DOI: 10.1111/j.1462-2920.2007.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and predictive modelling of Vibrio spp. in the Neuse River Estuary, North Carolina, USA

Abstract: Vibrio spp. are naturally occurring bacteria in marine and estuarine environments around the world. The genus includes several human and animal pathogens that can negatively impact human health, seafood and aquaculture. Vibrio spp. populations are capable of rapid adaptation in response to changing environmental conditions, making them dynamic over short-term and seasonal scales. Temperature, vertical mixing, tidal flushing, climate, precipitation and nutrient loading can change the estuarine environment and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 38 publications
6
75
3
Order By: Relevance
“…Whether this was due to shifts in eukaryotic plankton or other water parameters remains unknown. Indeed, chemical parameters differed considerably among Table 2), and Vibrio abundance can be strongly correlated with temperature (Heidelberg et al, 2002;Randa et al, 2004;Thompson et al, 2004;Hsieh et al, 2008). Overall, our results show that when populations are recovered at similar relative abundances in consecutive years, the habitat predictions are robust and reproducible, suggesting that similar stages of defined population cycles or lifestyles were sampled (for example, bloom versus attachment to a specific host).…”
Section: Resultsmentioning
confidence: 48%
“…Whether this was due to shifts in eukaryotic plankton or other water parameters remains unknown. Indeed, chemical parameters differed considerably among Table 2), and Vibrio abundance can be strongly correlated with temperature (Heidelberg et al, 2002;Randa et al, 2004;Thompson et al, 2004;Hsieh et al, 2008). Overall, our results show that when populations are recovered at similar relative abundances in consecutive years, the habitat predictions are robust and reproducible, suggesting that similar stages of defined population cycles or lifestyles were sampled (for example, bloom versus attachment to a specific host).…”
Section: Resultsmentioning
confidence: 48%
“…Field studies conducted worldwide over the last 40 years have shown such a relationship (42,43,44,45). As an example, results from different studies conducted over the period from 1995 to 2004 along the central-northern Italian Adriatic coast (46,47,48,49) showed that culturable vibrios (mainly the species Vibrio alginolyticus) were abundant in this area during the warmest months, when SST ranged from about 18°C to about 25°C.…”
Section: Effect Of Increasing Sst On Vibrio Growth and Biology: Fieldmentioning
confidence: 99%
“…Although these studies have not focused on the top three human pathogens, they are important because they shed light on the ecology of naturally occurring vibrios and because of the relationships with pathogens with which they may exchange genetic material. Positive relationships have been described between temperature and total vibrios in the waters of Germany (58,59), North Carolina (31,55,60,61), the country of Georgia (62), the state of Georgia (63), Italy (64,65), South Africa (66), and Germany (47). Interestingly, negative correlations have also been described between temperature and total vibrios in the waters of India (46,67) and Louisiana (68).…”
Section: Other Vibriosmentioning
confidence: 99%